Temporal trends in severe malaria in Chittagong, Bangladesh. - Maude, R; Hasan, M; Hossain, M; Sayeed, A; Kanti Paul, S; Rahman, W; Maude, R; Vaid, N; Ghose, A; Amin, R; Samad, R; Yunus, E; et al. (2012)
BACKGROUND: Epidemiological data on malaria in Bangladesh are sparse, particularly on severe and fatal malaria. This hampers the allocation of healthcare provision in this resource-poor setting. Over 85% of the estimated 150,000-250,000 annual malaria cases in Bangladesh occur in Chittagong Division with 80% in the Chittagong Hill Tracts (CHT). Chittagong Medical College Hospital (CMCH) is the major tertiary referral hospital for severe malaria in Chittagong Division. METHODS: Malaria screening data from 22,785 inpatients in CMCH from 1999-2011 were analysed to investigate the patterns of referral, temporal trends and geographical distribution of severe malaria in Chittagong Division, Bangladesh. RESULTS: From 1999 till 2011, 2,394 malaria cases were admitted, of which 96% harboured Plasmodium falciparum and 4% Plasmodium vivax. Infection was commonest in males (67%) between 15 and 34 years of age. Seasonality of malaria incidence was marked with a single peak in P. falciparum transmission from June to August coinciding with peak rainfall, whereas P. vivax showed an additional peak in February-March possibly representing relapse infections. Since 2007 there has been a substantial decrease in the absolute number of admitted malaria cases. Case fatality in severe malaria was 18% from 2008-2011, remaining steady during this period.A travel history obtained in 226 malaria patients revealed only 33% had been to the CHT in the preceding three weeks. Of all admitted malaria patients, only 9% lived in the CHT, and none in the more remote malaria endemic regions near the Indian border. CONCLUSIONS: The overall decline in admitted malaria cases to CMCH suggests recent control measures are successful. However, there are no reliable data on the incidence of severe malaria in the CHT, the most endemic area of Bangladesh, and most of these patients do not reach tertiary health facilities. Improvement of early treatment and simple supportive care for severe malaria in remote areas and implementation of a referral system for cases requiring additional supportive care could be important contributors to further reducing malaria-attributable disease and death in Bangladesh.